PENERAPAN SEKOLAH KETERAMPILAN DAN KEWIRAUSAHAAN MENGGUNAKAN KURIKULUM MUSLIMPRENEUR DAN SMART CLASS SYSTEM - Arsyad, Aisyah Tiar; Nurlatifah, Hanny; Samiono, Bambang Eko; Yusuf, Andi Mukramin; Shabir, Achmad (Universitas Padjadjaran, 2026)
This training program aims to increase the understanding and skills of Muslimpreneur value-based entrepreneurship among 100 participants from Pameungpeuk Subdistrict, Bandung Regency, the majority of whom are students and alumni of Al Marwah Vocational School. Activities include building smart-class-system-based classroom infrastructure, Muslimpreneur curriculum training, and pre-test and post-test surveys. The results of the training showed a significant increase in participants' understanding of aspects such as Muslimpreneur, entrepreneurship, marketing, halal products, and sharia finance, despite technical difficulties such as unstable electricity and licensing issues related to imported equipment. This program succeeded in producing 20 products with business concepts that were ready to be incubated at the Tajeer Incubator at Universitas Al Azhar Indonesia (UAI) and graduated 100 participants with competency certification, creating a strong foundation for the sustainability of micro-enterprises based on religious and technical values.Program pelatihan ini bertujuan meningkatkan pemahaman dan keterampilan kewirausahaan berbasis nilai Muslimpreneur bagi 100 peserta dari Kecamatan Pameungpeuk, Kabupaten Bandung, yang mayoritas merupakan siswa dan alumni SMK Al Marwah. Kegiatan mencakup pembangunan infrastruktur kelas berbasis smart class system, pelatihan kurikulum Muslimpreneur, dan survei pre-test serta post-test. Hasil pelatihan menunjukkan peningkatan signifikan dalam pemahaman peserta pada aspek Muslimpreneur, kewirausahaan, pemasaran, produk halal, dan keuangan syariah, meskipun sempat terdapat kendala teknis seperti stabilitas listrik dan perizinan perangkat impor. Program ini berhasil menghasilkan 20 produk dengan konsep bisnis yang siap diinkubasi di Inkubator Tajeer Universitas Al Azhar Indonesia (UAI) dan meluluskan 100 peserta bersertifikasi kompetensi, menciptakan fondasi kuat untuk keberlanjutan usaha mikro berbasis nilai religius dan teknis.